Seasonal prediction of extreme precipitation events and frequency of rainy days over Costa Rica, Central America, using Canonical Correlation Analysis - Maldonado Mora, Tito José (2013)
Artículo científico -- Universidad de Costa Rica. Centro de Investigaciones Geofísicas, 2013